2007
DOI: 10.1111/j.1542-4758.2007.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnea in hemodialysis patients: Risk factors and effect on survival

Abstract: Clinical, demographic, and dialysis-related characteristics were obtained at baseline. Total and cardiovascular mortality was ascertained after a median follow-up of 34 months. The probability of sleep apnea was low in 79 (29%) patients, moderate in 116 (43%) patients, and high in 75 (28%) patients. Male gender (odds ratio [OR] 5.13, p<0.001), obesity (BMI >30, OR 7.58, p<0.01), and interdialytic weight gain (OR 1.72/kg change, p<0.004) were independently associated with a high probability of sleep apnea. A hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
17
2
Order By: Relevance
“…However, limited evidence exists as to whether sleep disorders increase the risk for death in patients with ESRD. A recent study of dialysis patients using a sleep questionnaire failed to demonstrate an association between sleep apnea and mortality (8), while another study using self-reported sleep quality scales found that the risk of death was significantly higher for dialysis patients with poor sleep quality (9). Although polysomnography is the gold standard for diagnosing sleep disorders, few studies using polysomnography have investigated this possible association.…”
mentioning
confidence: 97%
“…However, limited evidence exists as to whether sleep disorders increase the risk for death in patients with ESRD. A recent study of dialysis patients using a sleep questionnaire failed to demonstrate an association between sleep apnea and mortality (8), while another study using self-reported sleep quality scales found that the risk of death was significantly higher for dialysis patients with poor sleep quality (9). Although polysomnography is the gold standard for diagnosing sleep disorders, few studies using polysomnography have investigated this possible association.…”
mentioning
confidence: 97%
“…Therefore, it seemed to be possible that multifactorial mechanisms, such as improvement of extracellular fluid control, enhanced clearance of uraemic toxins and reduction of hypocapnea by correction of metabolic acidosis, are responsible for the improvement of OSA in nocturnal dialysis. A trend towards lower KT/V was observed in dialysis patients with OSA; however, the difference was not statistically significant and could be attributable to the generally higher body weight in this group [55]. Whether renal transplantation contributes to an improvement of the condition has not yet been completely clarified [56].…”
Section: Sleep Apnoea and Chronic Kidney Diseasementioning
confidence: 97%
“…Excess mortality in patients with OSA, while repeatedly demonstrated in the general population, has so far not been shown for persons with ESRD. In a prospective study including 270 HD patients, using a questionnaire to assess risk for OSA, no excess mortality was observed by the authors in the high or intermediate risk groups, though the authors concede that the study may have been underpowered [55]. Mortality studies of a sufficient sample size and using polysomnography rather than substitute methods to diagnose OSA are still missing.…”
Section: Sleep Apnoea and Chronic Kidney Diseasementioning
confidence: 99%
“…In patients with high JESS scores (≥16), lifestyle modifications such as exercise [37] and further evaluation of sleep disturbance would be warranted. Future studies are necessary to examine the causes of sleepiness and survival [38,39] and the impact of treatment of sleepiness on survival. Mechanisms of adverse effects of sleepiness on survival are unknown.…”
Section: Discussionmentioning
confidence: 99%